Persistent papillary membrane in Wistar laboratory rats ( Rattus Norvegicus, Albinus Variation, Wistar ) - Flor Diana Yokoay Claros Chacaltana; Karina Kamachi Kobashigawa; Ivan Ricardo Martinez Padua; Gisele Pereira Valdetaro; Marcela Aldrovani; José Luiz Laus (Ciência Rural)
ABSTRACT: The aim of this research was to evaluate the presence of persistent pupillary membrane (PPM) in rats. Thirty rats between three and four months of age and weighing 300-500 grams, provided by the biothery section of the General Administration at Universidade Estadual Paulista (UNESP), Botucatu, SP, Brazil, were subjected to ophthalmological examination by slit lamp biomicroscopy, fluorescein eye stain test and rebound tonometry. We found PPM with possible hereditary origin in 15 animals (50%).